Policing sexuality: Sexual minority youth, police contact, and health inequity - Gabriel L. Schwartz; Jaquelyn L. Jahn; Amanda Geller (Elsevier, 2022)
Police contact is increasingly recognized as an adverse childhood experience and determinant of poor mental health. While targeting of LGBTQ sex and community spaces by law enforcement has a long precedent in US history-and while LGBTQ people continue to protest unfair police treatment-little population-level research has examined police contact disparities by sexual orientation or gender identity. We test whether sexual minority (SM) youth have higher risk of police contact through young adulthood. We analyze a nationally representative cohort of >15,000 US young adults who were in middle/high school in the mid-1990s, with police contact histories collected at age 18-25. Using four different, equally reasonable approaches to coding youth-reported sexual orientation, we identified ∼500-1900 SMs. Compared to heterosexual youth, SM youth had 1.86 times the odds of ever being stopped by police (95% CI = 1.56-2.22, p < 0.001), were stopped 1.60 times as often (CI = 1.38-1.86, p < 0.001), and were stopped at younger ages (survival time ratio = 0.91, CI = 0.88-0.93, p < 0.001). Inequities were particularly driven by SM women, among whom disparities were severe (ever stopped OR = 2.18, stop count ratio = 2.44, survival time ratio = 0.87). For men, inequities only emerged once a broad definition of SM was adopted, suggesting that young SM men who do not identify as LGB (or who are reticent to report themselves as such) may be at particular risk. Results were robust to adjustment for race/ethnicity and parental nativity, though small cells meant models stratified by race/ethnicity were underpowered.Given substantially heightened police contact among SM youth (particularly, young SM women), care providers and educators working with them should explicitly combat homophobic and criminal legal system stigma and screen for police contact and its psychological sequelae. More data on LGBTQ communities' criminal legal system contact throughout life is essential for preventing the causes and consequences of related sexual orientation-based health inequities.